Prospective nonrandomized analytical comparative study of clinicoradiological relationship and quality of life between lumbar interbody fusion and posterolateral lumbar fusion - Agrawal, Rati; Saroha, Arun; Jain, Vijendra; Walia, Bipin (Asian Journal of Neurosurgery, 2020)
Study Design: This prospective, nonrandomized, analytic comparative study analyzed the outcome of 100 patients who underwent spinal fusion surgeries (Posterolateral fusion (PLF) and posterior lumbar interbody fusion [PLIF]) with 6 months of follow-up. Objective: The aim of our study was to compare clinicoradiological outcome of the lumbar spinal fusion surgeries (PLF vs. PLIF/transforaminal lumbar interbody fusion [TLIF]), to assess the quality of life pre- and post-operatively in all patients, and to compare the results within the groups. Summary of Background Data: We retrieved the articles related to posterolateral fusion (PLF) and PLIF/TLIF through computer-assisted PubMed and Cochrane database search. Most of the studies in previous literature did not show any significant difference in the success of fusion between the two groups. However, the global outcome in terms of clinical and radiological parameters was good in all the studies. Materials and Methods: Senior neurosurgeons who are part of the study treated 100 patients presented with degenerative disc disease (DDD). Patients underwent two types of spinal fusion surgeries: Posterolateral fusion (PLF) and PLIF/TLIF, and those two groups were compared for clinicoradiological outcome, successful fusion, and quality of life at 6 months of follow-up. Results were analyzed statistically using SPSS version 21.0 and presented in terms of frequency, percentage, mean, and standard deviation. Measurements were compared between groups using the Student's t-test (independent and paired) for normally distributed variables. Percentage was compared with Chi-square test in various parameters. Statistical significance was determined with P values; P < 0.05 was considered statistically significant. Results: Patients aged between 30and 65 years with lumbar DDD who met the inclusion criteria were included in the study. Patients were operated for 1–3 vertebral levels and showed clinical satisfactory outcome on visual analog scale (P = 0.004) and modified-Oswestry low back pain disability questionnaire (Oswestry disability index) (P = 0.000) at 6 months as compared to the preoperative data, which was statistically significant. Radiological outcome in terms of lumbar lordotic angle (LLA, P = 0.000) and ratio of disc space height (DSH) and height of immediate superior vertebral body (P = 0.000) at 3 months of follow-up was also statistically significant. All of our patients showed a well-placed implant (screws and cage) in the follow-up period. Our patients showed successful fusion more in the PLIF group (81.25%) as compared to the PLF group (67.30%), but those results are not statistically significant (P = 0.112), and all of our patients showed statistically significant difference (P = 0.000) in quality of life score at 6 months of follow-up when compared with the preoperative score. Conclusions: We concluded from our study and after the review of literature that the patients with lumbar DDD should undergo spinal instrumentation surgery either PLF or PLIF as per the requirement as these surgeries provide good clinical and radiological outcomes in terms of pain, disability index, LLA, and maintenance of DSH. Although both the groups have few degrees of risks and complications, these are not major one and can be managed easily. The fusion rates are similar in both the groups (PLF and PLIF). Quality of life index showed significant difference within 1 week, after 3 months, and after 6 months of surgery in all of our patients.
Keywords: Degenerative disc disease; lumbar lordotic angle; Oswestry disability index; posterior lumbar interbody fusion; posterolateral fusion; quality of life score; transforaminal lumbar interbody fusion; visual analog scale